IL-23 Contributes to Control of Chronic Helicobacter Pylori Infection and the Development of T Helper Responses in a Mouse Model1 - Horvath, Dennis J.; Washington, Mary K.; Cope, Vicki A.; Scott Algood, Holly M. (Frontiers in Immunology, 2012)
The immune response to Helicobacter pylori involves a mixed T helper-1, T helper-2, and T helper-17 response. It has been suggested that T helper cells contribute to the gastric inflammatory response during infection, and that T helper 1 (Th1) and T helper 17 (Th17) subsets may be required for control of H. pylori colonization in the stomach. The relative contributions of these subsets to gastritis and control of infection are still under investigation. Expression of IL-23, which is induced in dendritic cells and macrophages following co-culture with H. pylori, has also been reported to increase during H. pylori infection in humans and animal models. IL-23 plays a role in stabilizing and expanding Th-17 cell cytokine expression. To investigate the role of IL-23 in H. pylori, we infected IL-23 deficient mice and wild-type littermates with H. pylori strain SS1. At various time points post-infection, we assessed colonization, gastric inflammation, and cytokine profiles in the gastric tissue. Specifically, H. pylori-infected IL-23-/- mice have higher levels of H. pylori in their stomachs, significantly less chronic gastritis, and reduced expression of IL-17 and IFN-gamma compared to H. pylori-infected wild-type mice. While many of these differences were significant, the H. pylori infected IL-23-/- had mild increases in our measurements of disease severity. Our results indicate that IL-23 plays a minor role in the activation of the immune response and induction of gastritis in response to H. pylori by contributing to the control of infection and severity of gastritis.